2014
DOI: 10.1159/000358674
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine Promotes MDA-MB-231 Cell Migration and Invasion through Increased ROS-Dependent HIF-1a Accumulation

Abstract: Background/Aim: Deferoxamine (DFO), an iron chelator, has been reported to induce hypoxia-inducible factor-1α (HIF-1α) expression. HIF-1α plays a critical role in promoting tumor metastasis. However, the molecular mechanisms underlying induction of HIF-1α in breast cancer cells remain unknown. Our aim was to ascertain whether DFO enhanced cancer metastasis in MDA-MB-231 cells. Methods: Cellular reactive oxygen species (ROS) was measured by flow cytometry. Cell migration was determined by wound healing and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 39 publications
2
43
0
2
Order By: Relevance
“…Although multiple studies reported that accumulation of ROS regulated autophagy by pathways such as: i) oxidization of ATG4 leading to accumulation of autophagosomes; ii) activation of the AMPK signaling cascade inducing the initiation of autophagy through the ULK1 complex; iii) disruption of BECN1-BCL-2 interaction leading to the initiation of autophagy; or iv) alteration of mitochondria homeostasis leading to mitophagy activation (75). Furthermore, reactive oxygen/nitrogen species (ROS/RNS) generated in the context of radiation exposure are essential activators of cytoplasmic signaling cascades such as p38 MAPK, JNK, HIF-1α, which play essential roles in the regulation of autophagy (91).…”
Section: Ros and Autophagymentioning
confidence: 99%
“…Although multiple studies reported that accumulation of ROS regulated autophagy by pathways such as: i) oxidization of ATG4 leading to accumulation of autophagosomes; ii) activation of the AMPK signaling cascade inducing the initiation of autophagy through the ULK1 complex; iii) disruption of BECN1-BCL-2 interaction leading to the initiation of autophagy; or iv) alteration of mitochondria homeostasis leading to mitophagy activation (75). Furthermore, reactive oxygen/nitrogen species (ROS/RNS) generated in the context of radiation exposure are essential activators of cytoplasmic signaling cascades such as p38 MAPK, JNK, HIF-1α, which play essential roles in the regulation of autophagy (91).…”
Section: Ros and Autophagymentioning
confidence: 99%
“…As shown in a previous study, DFO induces hypoxia and the consequent expression of hypoxiainducible factor-1 alpha (HIF-1α) in breast cancer cells [15]. HIF-1α initiates the transcription of genes encoding angiogenesis-promoting proteins such as vascular endothelial growth factor [16].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated subunit HIF-1α in the cellular nucleus and cytoplasm further regulates the expression of several target genes that are engaged in neuroprotection, erythropoiesis, and apoptosis modulation in protecting tissues against hypoxic conditions [14][15][16][17]. Furthermore, inadequate oxygen supply likely appears in the brain regions while ICH occurs and abnormalities of HIF-1α are also observed in diabetes.…”
Section: Introductionmentioning
confidence: 99%